Community perception and utilization of raru in Bonalumban Village. Issue 1 (November 2021) - Rangkuti, A B; Susilowati, A; elfiati, D; Zaitunah, A; Samsuri; Iswanto, A H; Rambey, R; Sucipto, T; Hakim, L; Azhar, I; Syahputra, O K H; Harahap, M M; et al.
Abstract: Village life around the forest is inseparable from the existence of the forest. The use of raru as a forest product has been passed down from generation to generation in the community of Bonalumban Village, Tukka District, Central Tapanuli Regency, North Sumatra. The study of community perceptions and dependencies on Raru in Bonalumban village is needed to determine the potential of raru and encourage efforts to preserve raru. The method of selecting respondents is done by purposive sampling by selecting general respondents and specialized respondents. Data analysis uses descriptive statistics. Public perceptions about the existence of raru in nature are still plentiful so there is no public effort to regenerate. Community dependency on raru is grouped into four categories, that is for sale, palm wine concoctions, animal cages, and building materials. Raru harvesting activities by felling without being accompanied by cultivation activities causes the presence of raru vegetation to decrease.